Pengaruh Pengungkapan Enterprise Risk Management terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderasi - Anni Fitriyani Munawwaroh; Nur Fatoni; Warno Warno (Eksos, 2021)
This study aims to analyze the influence of Enterprise Risk Management (ERM) on firm value by testing profitability in strengthening or weakening the relationship between Enterprise Risk Management (ERM) and firm value and testing leverage in controlling the relationship between Enterprise Risk Management (ERM) on firm value. in service companies listed on the Indonesian Syari'ah Stock Index (ISSI) 2015 – 2019. The population of this study are service companies listed on the Syari'ah Stock Index (ISSI) 2015 – 2019 as many as 51 companies. The sample selection in this study used a purposive sampling method and 10 companies were selected. Data analysis used the Structural Equation Modeling – Partial Least Square (PLS) method which was run using SmartPLS 3.0 software. The results showed that Enterprise Risk Management (ERM) and Profitability could not affect the Company Value. Profitability cannot strengthen or weaken the relationship between Enterprise Risk Management (ERM) and Company Value. Meanwhile, leverage can control the effect on firm value.